Transcriptomic profile of host response in Japanese encephalitis virus infection - Gupta, Nimesh (BioMed Central, 2011)
BACKGROUND: Japanese encephalitis (JE) is one of the leading causes of acute encephalopathy with the highest mortality rate of 30-50%. The purpose of this study was to understand complex biological processes of host response during the progression of the disease. Virus was subcutaneously administered in mice and brain was used for whole genome expression profiling by cDNA microarray. RESULTS: The comparison between viral replication efficiency and disease progression confirms the active role of host response in immunopathology and disease severity. The histopathological analysis confirms the severe damage in the brain in a time dependent manner. Interestingly, the transcription profile reveals significant and differential expression of various pattern recognition receptors, chemotactic genes and the activation of inflammasome. The increased leukocyte infiltration and aggravated CNS inflammation may be the cause of disease severity. CONCLUSION: This is the first report that provides a detailed picture of the host transcriptional response in a natural route of exposure and opens up new avenues for potential therapeutic and prophylactic strategies against Japanese encephalitis virus.